Preliminary study on sensory design for ASD : autistic classroom / Roslinda Ghazali, Siti Rasidah Md Sakip and Ismail Samsuddin - Ghazali, Roslinda; Md Sakip, Siti Rasidah; Samsuddin, Ismail (2018)
Autism Spectrum Disorders (ASD) refers to a range of condition characterized by challenges with social skills, repetitive behaviors, speech and nonverbal communication as well as unique strengths and differences of a child. The child can survive independently, continue their routine lives and exhibit regular development in the future with the support and encouragement in order to continue their education in different learning environment. Every ASD child is unique and has his or her own combination of characteristics. Unpredictable disruptive behaviors among autistic child could occur in the classroom. Autistic people may appear to behave unusually and they can meltdown when they are in difficulties situation. The impact of sensory differences in people with Autism has been recognized recently. Therefore, designated learning environment should consider sensory issues to overcome their needs. Architects are responsible to provide a design that responds to the needs of all members of society. However, they lack awareness of sensory issues regarding the built environment in the daily life of an individual with autism prior to designing stage especially in terms of safety and security for autism. Thus, this research objective is to identify the criteria of sensory design in the classroom for autism. Developing the Design Criteria Checklist of sensory design for Autism Centre is the aim of this paper. It is hoped thatthis Design Criteria Checklist is part of benchmarking tool that can be usedin identifying the design criteria for autism classroom. The preliminary site visit was conducted accordingly to ensure relevant variables are met in the literature. The result has highlighted the criterion factors that are related to the quality of the physical learning environment and was considered at early design phase. It is hoped that this paper could contribute tlo architects and designers to utilize this Design Criteria Checklist of sensory design during the design stage and create a quality environment for autistic children in Malaysian. Therefore, the paper intends to measure the conduciveness of environment for autism as well assuggestion on the benefits of creating a conducive learning environment which not only optimize the classroom environment but also fulfill the parent’s satisfaction.